PENGARUH GAYA KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. CARAKA PILAR MANDIRI - Ubaid Al Faruq; Amin Kuneifi El Fachmi; Herry - Suherman (Program Studi Pendidikan Ekonomi Universitas Pamulang, 2017)
ABSTRACT The purpose of this research is to find out and analyze the influence of leadership styles and discipline work against employee productivity PT. Caraka Pilar Mandiri either by itself or together significantly, it also aims to find out the dominant variables against work productivity.This research is a research eksplanatori who try to test the hypothesis are statistically based on the empirical data from the respondents and explain it in descriptive and inferensial. The population of the research was an employee of PT. Caraka Pilar Mandiri totalling 102 people sampling method with saturated. Hypothesis testing is carried out by multiple linear regression analysis.Research results can be summed up as follows : (1) Acquired Fhitung of 26,989 with significance of 0.000. While the value of Ftabel on the level of confidence of 95% (α = 5%) was 3,088. That means that the leadership style (X1) and discipline work (X2) together influential very significantly to the productivity of employees at PT Caraka Pilar Mandiri. (2) Test results received a obtained the value of the coefficient of determination R2 of 0.353, which indicates that a variable work discipline and leadership style has the ability to explain its effects on employee productivity variable of 35.5% while the rest amounted to 64.5% is the influence of other free variables not examined in this study. (3) Test results between leadership style with work productivity are obtained coefficient determination (R2) of 0,196 which means that the free variables influence leadership style against the variable work productivity is of 19.6%. (4) Test results between the discipline of working with work productivity obtained coefficients of determination (R2) of 0.304 which means that the influence of the working discipline against the variable work productivity is of 34.7%. Keywords: Leadership Styles, Discipline, Productivity